IMPLEMENTATION OF RPP MERDEKA BELAJAR THROUGH PEER COLLABORATION AT SD NEGERI 61 BANDA ACEH - Sri Rahayu Hariani Br Tumangger; Febrianaz Syafa; Hapidah; Salma Ara; Muhammad Bahagia; Dr. Siti Mayang Sari, M.Pd; Sukma Wulanda (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses a descriptive qualitative research method, which is researching based on phenomena that occur in collaboration at SD Negeri 61 Banda Aceh. Based on the facts seen in the school that teachers have used the Merdeka Curriculum in the thematic learning process. Researchers observed the learning carried out by teachers of SD Negeri 61 Banda Aceh that thematic learning provides opportunities for teacher creativity in the active learning process. Through this research method, it will be described transparently to produce the application of integrative thematic learning in a collaborative manner. It is known that the curriculum used in the school has partly used the learning curriculum so that the learning process carried out is quite good and significant with the results obtained by students in integrative thematic learning. SD Negeri 61 Banda Aceh has implemented the Merdeka Curriculum in grades 1 to 4. While grades 5 and 6 still use the 2013 Curriculum. In preparing lesson plans, teachers find it difficult because, it is very different from the 2013 curriculum. Then at SD Negeri 61 Banda Aceh school rarely do socialization.